EVALUATION OF CASH FLOW REPORT AS AN INVESTMENT DECISION MAKING SUPPORT IN CV. CAHAYA MENTARI IN MAKASSAR - Nurwanah, Andi (Universitas Patria Artha, 2018)
The cash flow statement has long been required to be made as part of the company's mainfinancial statements in America based on the Standard of Financial Accounting StatementNo.95 Statement of Cash Flows issued by the Financial Accounting Standards Board. For users of financial statements, especially investors, many benefits can be obtained from this report. Butmany people still don't know this. Usually they only take the data contained in the balance sheetand income statement only to conduct an evaluation in assessing the company's performance.CV. Cahaya Mentari has presented a cash flow statement. The report has been presented wellusing the indirect method. From the cash flow statement CV. Cahaya Mentari has an increasingnet cash flow. However, the company's net cash flow shows a negative number due to a largeamount of cash users in investment activities.